Protective effects of S-allyl cysteine on behavioral, morphological and biochemical alterations in rats subjected to chronic restraint stress: Antioxidant and anxiolytic effects. (August 2017) - Becerril-Chávez, Hugo; Colín-González, Ana Laura; Villeda-Hernández, Juana; Galván-Arzate, Sonia; Chavarría, Anahí; Eduarda de Lima, María; Túnez, Isaac; Santamaría, Abel
Highlights: Chronic restraint stress increases brain oxidative damage. Behavioral and morphological changes were produced in stressed rats. Chronic administration of S-allyl cysteine protected rats from stress. Regional biochemical changes in the brain afforded this protection. Abstract: S-allyl cysteine (SAC) is a garlic-derived compound with antioxidant properties. Restraint stress constitutes a rodent model mimicking different features of human stress. The effects of SAC on behavioral, biochemical and morphological endpoints of brain alterations induced by chronic restraint stress were evaluated in rats. Restraint stress sessions were performed every day for 6 h during 21 consecutive days. SAC (100 mg/kg, i.p.) was administered daily 30 min before every single stress session. Behavioral tests comprised anxiety-like and depression-like challenges. Biochemical and morphological endpoints were estimated in three brain regions: striatum, hippocampus and cortex. Stressed animals exhibited augmented anxiety-like behavior, depression and morphological alterations, and these changes were accompanied by increased oxidative damage, compensatory regulation of antioxidant enzymes, and increased corticosterone plasma levels. SAC prevented anxiety-like behavior elicited by chronic stress in rats, and reduced morphological and biochemical alterations. The protective actions of SAC are related to its antioxidant properties.